Coalesce of artificial intelligence and human resource management: a conceptual study - Muralidhar, Shubha; Bharadwaj, Aishwarya; Bhat K, Prathima (BOHR International Journal of Advances in Management Research, 2023)
Artificial Intelligence (AI) is a pattern recognition, which is used in resource matching. It is the theory and development of computer systems with the ability to perform tasks that normally require human intelligence, such as visual perception, speech recognition, decision-making, and translation between languages. AI has grown exponentially in the past decade and is assisting managers to make better and quick decisions with precision. The application of AI in different sectors has been predominant and its role in Human Resource Management (HRM) has been profound. Growing competition worldwide has made it important to automate the process of HRM. AI has created a disruption as it has displaced an established process with an innovative one. This is a conceptual study with an attempt to understand the role of AI in various activities of HRM. It also highlights the scope of AI in recruitment and selection, workforce management, and learning and development.